2020
DOI: 10.1097/hcr.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Talk Test as a Method to Estimate Ventilatory Threshold and Guide Exercise Intensity in Cardiac Patients

Abstract: Purpose: To determine the relationship between the Talk Test (TT) and ventilatory threshold (VT) in patients with cardiac disease and to compare the TT with exercise intensity guidelines. Methods: Twenty cardiac patients, aged 65 ± 8.5 yr, performed 2 exercise tests with identical ramp protocols on a cycle ergometer on the same day. One test was a submaximal effort to assess exercise intensity using the TT. The other was a cardiopulmonary exercise test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…23 The TT asks the participants how comfortable they feel speaking during exercise, and its use has been associated with low (≤2 mmol/L; speaking comfortably ), moderate (~3–4 mmol/L; not speaking comfortably ) and high (>5 mmol/L; unable to speak comfortably ) levels of BLa during continuous aerobic type exercise, and has a close relationship with RPE 24 and VT1 or gas exchange threshold. 25 Moreover, the use of the TT can be extended to different populations, including cardiac patients, 26 overweight and obese people 27 and elite athletes, 28 where the use of an analogue scale can strengthen this approach. 27 However, it is important to highlight that the RPE and TT must be approached individually according to the type of exercise prescribed.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…23 The TT asks the participants how comfortable they feel speaking during exercise, and its use has been associated with low (≤2 mmol/L; speaking comfortably ), moderate (~3–4 mmol/L; not speaking comfortably ) and high (>5 mmol/L; unable to speak comfortably ) levels of BLa during continuous aerobic type exercise, and has a close relationship with RPE 24 and VT1 or gas exchange threshold. 25 Moreover, the use of the TT can be extended to different populations, including cardiac patients, 26 overweight and obese people 27 and elite athletes, 28 where the use of an analogue scale can strengthen this approach. 27 However, it is important to highlight that the RPE and TT must be approached individually according to the type of exercise prescribed.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…Intensity of aerobic PA can be measured by different methods. Previous work has provided guidance on assessment of PA intensity, such as the talk test [ 48 , 49 , 50 ], heart rate monitoring by using wearable devices [ 51 , 52 , 53 , 54 ], metabolic equivalent (MET) [ 28 ], and rating of perceived exertion (RPE) [ 55 , 56 ]. Each method has different limitations and benefits that should be considered by the patient and/or the exercise professionals with whom they are working.…”
Section: Physical Activity Prescriptionmentioning
confidence: 99%
“…From these findings, the studies proposed the TT+ stage as a prescription parameter and identified its usefulness in most of the individuals evaluated [18,27,35]. Sorensen et al [34] found correlations between the TT stages and VT 1 from 0.37 to 0.60. Also, it was observed that individuals are unlikely to show electrocardiographic signals of myocardial ischemia at the load corresponding to the time they can still speak comfortably (TT+) [28].…”
Section: Measurement Propertiesmentioning
confidence: 99%